Comparative evaluation of different spawn substrates on the growth and yield of oyster mushroom - Verma, Parul; Nath, Manoj; Sharma, Annu; Barh, Anupam; Kamal, Shwet; Sharma, Ved Prakash; Kumar, Anil (Mushroom Research, 2023)
Oyster mushroom is well known for its nutritional quality and ease in cultivation. The spawn quality is major determining factor to obtain the maximum yield in different mushroom. Wheat grain is popular in spawn industry for the preparation of the spawn. The continuous use of the wheat grain for spawn preparation can lead to the food security. Therefore, utilization of the alternative spawn substrate for the spawn preparation is one of the major concern in mushroom industry. In this study, we have investigated the growth and yield related parameters of oyster mushroom using the wheat straw and liquid spawn as a substrate. Delayed spawn run, pin head formation and days of first harvest was recorded in the wheat straw spawn as compared with control i.e. wheat grain spawn in both oyster mushroom species viz. Pleurotus djamor and P. ostreatus var. florida. Notably high yield was observed in the control (P. djamor: 77.76% and P. ostreatus var. florida 79.84%) than wheat straw spawn (P. djamor: 66.73% and P. ostreatus var. florida: 72.15 %). Notably, the average fruit body weight, diameter of pileus and stipe was higher in the wheat straw spawn as compared with control in P. ostreatus var. florida. Moreover, the results of the liquid spawn analysis in P. djamor indicates the earlier spawn run and pin head formation in control as compared with liquid spawn. Though, the yield was higher in control (68%) than liquid spawn (54%). Overall the findings of this study will be helpful to promote the alternative spawn substrates in the oyster mushroom cultivation.